Multi‐walled carbon nanotubes applied through seed‐priming influence early germination, root hair, growth and yield of bread wheat (Triticum aestivum L.). (25th January 2018) - Joshi, Anjali; Kaur, Simranjeet; Dharamvir, Keya; Nayyar, Harsh; Verma, Gaurav
Abstract: BACKGROUND: Reports of multi‐walled carbon nanotubes (MWCNTs) incorporated into plants have indicated better yield and productivity, yet the phenomena need in‐depth understanding especially when agricultural crops are tested. We primed wheat seeds with MWCNTs to understand the effects on germination, growth, anatomy, physiology and yield. RESULT: This study, carried out in field conditions, is a step forward over the previous reports. Early germination, excessive root hair, denser stomata and larger root length result in faster growth and higher yield of wheat plants. Denser root hair facilitated the uptake of both water and essential minerals such as phosphorus (P) and potassium (K), which boosted the crop yield by significantly improving grain yield per plant from 1.53 to 2.5 g, a 63% increase. Increase in cell elongation by 80% was recorded, while xylem and phloem sizes dilated to almost 83% and 85% of control, thus enhancing their capacity to conduct water and nutrients. CONCLUSION: Augmented growth of MWCNT‐primed wheat, enhancement in grain number, biomass, stomatal density, xylem–phloem size, epidermal cells, and water uptake is observed while finding no DNA damage. This opens up an entirely new aspect to using cost‐effective nanomaterials (the MWCNTs were produced in‐house) for enhancing the performance of crop plants. © 2017 Society of Chemical Industry